A Sterility Induction Trait in the Genic Male Sterility Wheat Line 4110S Induced by High Temperature and its Cytological Response. Issue 5 (2nd July 2018) - Yang, Xuetong; Geng, Xingxia; Liu, Zihan; Ye, Jiali; Xu, Mengfan; Zhang, Lingli; Song, Xiyue
Abstract : Male sterility has an essential role to exploit heterosis. In particular, the development of the photo‐thermosensitive male sterility system has accelerated hybrid wheat ( Triticum aestivum L.) breeding. In this study, we obtained a novel thermosensitive genic male sterility (TGMS) wheat line 4110S, where its fertility was sensitive to temperature during the later uninucleate stage and the line was completely male sterile when the average temperature exceeded ∼20°C. Phenotypic and cytological analyses detected morphologically distinct hallmarks of fertility‐to‐sterility conversion in the anther during the trinucleate stage. Delayed programmed cell death in the tapetum affected microspore development and caused defective pollen exine formation, which ultimately resulted in male sterility. The TGMS line could be used in the two‐line hybrid production systems, where it can maintain male sterility via self‐pollination at low temperatures and can be crossed with a pollen donor to produce hybrid wheat seeds at higher temperatures. Our findings provide a better understanding of the mechanisms responsible for male sterility in wheat, thereby facilitating production of hybrid wheat seed.